Book Review: The human predicament by David Benatar - Gonçalves Oliveira, André Mário (Sofia, 2026)
BENATAR, David. The Human Predicament: a candid guide to life's biggest questions. Nova Iorque: Oxford University Press, 2017.
Keywords: David Benatar; antinatalism; the human predicament